Social Media Branding Strategies that Strengthen School Image Among Stakeholders: Strategi Branding Media Sosial yang Membangun Citra Positif Sekolah - Yekti Eriani; Amrozi Khamidi; Kaniati Amalia; Mochamad Nursalim (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In the digital era, social media has become a key medium for communication and institutional promotion. Specific Background: Educational institutions increasingly utilize these platforms to build and manage their public image. Knowledge Gap: However, there is limited comprehensive synthesis of effective branding strategies specifically tailored to the educational context through social media. Aims: This study aims to explore and analyze branding strategies via social media to construct institutional image, with a focus on educational settings. Results: Using a qualitative approach and literature study method, the research reviews 19 national and international peer-reviewed articles on educational branding through social media. The analysis identifies key strategies including consistent visual identity, interactive content, storytelling, and community engagement. These elements contribute to improved public perception, stronger institutional identity, and increased stakeholder trust. Novelty: The study offers a synthesized, literature-based framework of digital branding practices applicable to schools, bridging theoretical insights with practical application. Implications: The findings provide actionable guidance for educational institutions, particularly in optimizing social media as a branding tool to enhance image, attract students, and remain competitive in an increasingly digital educational landscape. Highlights: Social media shapes school identity and public perception. Key strategies include visual consistency, storytelling, and interaction. Literature synthesis offers practical guidance for digital branding. Keywords: Social Media Branding, Educational Institutions, School Image, Digital Identity, Community Engagement